Figuring Out the Figurines of the Ancient Near East - Stephanie Langin-Hooper (Les Carnets de l’ACoSt)
We are pleased to announce the publication of Figuring Out the Figurines of the Ancient Near East, edited by Stephanie Langin-Hooper. This is the first volume in the series Occasional Papers in Coroplastic Studies that is designed to provide a forum for the publication of peer-reviewed papers dedicated to coroplastic research. This series is published by ACoSt. This present volume of 80 pages comprises 4 papers that were delivered at one of the three sessions of the Annual Meeting of the American Schools of Oriental Research (ASOR) either in 2009, 2010, or 2011 that were entitled “Figuring Out the Figurines of the Ancient Near East”. These were organized by Stephanie Langin-Hooper.